Experimental Study of the Surface Dielectric Strength of Insulating Tubes under Lightning Impulse Voltages - Acharya, Akrit; Gautam, Basanta Kumar (Journal of Science and Engineering, 2025)
Lightning Protection Systems (LPS) safeguard structures, electrical systems, and personnel from lightning strikes. Insulating tubes, which support air terminals, play a critical role by providing electrical isolation and directing current safely. These tubes must withstand extreme lightning-induced shocks, often reaching hundreds of kilovolts. This study investigates insulating tubes of identical dimensions but different materials, analyzing the impact of material composition and voltage polarity on their performance. Testing under standardized lightning impulse voltages (1.2/50 µs) is conducted, as their behavior under rapid surges differs from steady-state conditions. Failure under impulse voltages can compromise the entire LPS. The findings enhance understanding of dielectric properties under both positive and negative lightning strikes, aiding in the selection of reliable materials for LPS applications. The effect of the material of the insulating tube is evaluated.